2013
DOI: 10.3402/polar.v32i0.11068
|View full text |Cite
|
Sign up to set email alerts
|

Ice volume changes (1936–1990–2007) and ground-penetrating radar studies of Ariebreen, Hornsund, Spitsbergen

Abstract: Ariebreen is a small (0.37 km 2 )-valley glacier located in southern Spitsbergen. Our ground-penetrating radar surveys of the glacier show that it is less than 30 m thick on average, with a maximum thickness of 82 m, and it appears to be entirely cold. By analysing digital terrain models of the ice surface from different dates, we determine the area and volume changes during two periods, 1936Á1990 and 1990Á2007. The total ice volume of the glacier has decreased by 73% during the entire period 1936Á2007, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In the interpolation, two different techniques available in ESRI ArcGIS 10.1 software were tested: Topo to Raster tool based on the ANUDEM algorithm, considered to be the most effective for creating hydrologically correct raster surface (Hutchinson 1989), and TIN to Raster tool -a linear interpolation triangulation procedure and Triangulated Irregular Network conversion to a 20 m x 20 m regular grid. The efficiency of both methods for glaciological research has been shown by numerous authors (Kohler et al 2007;Barrand et al 2010;Nuth et al 2010;Lapazaran et al 2013). The latter method gave superior results and is used here.…”
Section: Methodsmentioning
confidence: 79%
“…In the interpolation, two different techniques available in ESRI ArcGIS 10.1 software were tested: Topo to Raster tool based on the ANUDEM algorithm, considered to be the most effective for creating hydrologically correct raster surface (Hutchinson 1989), and TIN to Raster tool -a linear interpolation triangulation procedure and Triangulated Irregular Network conversion to a 20 m x 20 m regular grid. The efficiency of both methods for glaciological research has been shown by numerous authors (Kohler et al 2007;Barrand et al 2010;Nuth et al 2010;Lapazaran et al 2013). The latter method gave superior results and is used here.…”
Section: Methodsmentioning
confidence: 79%
“…Nuth and others, 2013), and has been reported for both the tidewater (Blaszczyk and others, 2013) and land-terminating glaciers (e.g. Lapazaran and others, 2013) of Hornsund.…”
Section: Study Areamentioning
confidence: 75%
“…Whereas, during the whole research period the slowing of this process reached only 5 ha in period 1973-1990 and average recession 3.7 ha per year in the years 1990-2013. The changes of glacier's areas and their front recession is observed in whole Svalbard, e.g another valley glacier located in southern Spitsbergen -Ariebreen [17] and others [18].…”
Section: Discussionmentioning
confidence: 99%